WOMEN’S OPPRESSIONS AS REFLECTED IN JORDAN BELFORT’S THE WOLF OF WALL STREET - BayuSatrya, Yudha (LANTERN (Journal on English Language, Culture and Literature), 2016)
This thesis discusses women’s oppression in Jordan Belfort’s memoir entitled The Wolf of Wall Street. The purposes of this thesis are to explain the forms of women’s oppression and the causes of women’s oppression in the memoir. In order to achieve the desired result, the writer uses library research to collect data and sociological approach by emphasizing feminism theory and oppression theory to analyze the data. The analysis shows the oppressed women, the forms of oppression, and the causes of oppression. Through the analysis, the writer concludes that there are three forms of oppression suffered by women and the cause of the oppression is financial dependency.